Performance Structure of Barongan Kademangan at the Barongan Kademangan Art Studio in Bonang Subdistrict Demak Regency - Fachrunnisa, Amaril; Kusumastuti, Eny; Tani Utina, Usrek (Universitas Negeri Semarang, 2025)
This study aims to describe and analyze the structure of the Barongan Kademangan performance as presented by the Barongan Kademangan Art Studio in Bonang Subdistrict, Demak Regency. This research employs a descriptive-analytic method with a qualitative approach. Data collection techniques include observation, interviews, documentation, and literature study. The findings reveal that Barongan Kademangan is a form of folk art that integrates elements of dance, traditional music, and theatrical performance, with the barong figure serving as the central focus. The performance is composed of distinctive elements such as movement, musical accompaniment, costume and makeup, props, as well as floor patterns and staging. In addition to serving as entertainment, Barongan Kademangan functions as a medium of social communication that fosters community bonding, reinforces local cultural identity, and acts as a means of preserving traditional values. Thus, this art form plays a vital role in strengthening social cohesion and deserves ongoing support for its preservation.